2012
DOI: 10.1364/oe.20.023610
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dark counts in optimized geometries for superconducting nanowire single photon detectors

Abstract: We have experimentally compared the critical current, dark count rate and photo-response of 100nm wide superconducting nanowires with different bend designs. Enhanced critical current for nanowires with optimally rounded bends, and thus with no current crowding, are observed. Furthermore, we find that the optimally designed bend significantly reduces the dark counts without compromising the photo-response of the device. The results can lead to major improvements in superconducting nanowire single photon detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…The strength of the suppression is dependent on the particular geometry of the superconducting structure as well as on the angle and the radius r of the bend and the ratio of the coherence length to the width of the strip ξ GL /w. Several experiments by different groups [29][30][31] have confirmed the predictions of [28]. It has been shown that the current crowding is stronger for wider superconducting strips but becomes weaker with an increase of the radius of the bend.…”
Section: Stationary State Of Snspdmentioning
confidence: 59%
See 1 more Smart Citation
“…The strength of the suppression is dependent on the particular geometry of the superconducting structure as well as on the angle and the radius r of the bend and the ratio of the coherence length to the width of the strip ξ GL /w. Several experiments by different groups [29][30][31] have confirmed the predictions of [28]. It has been shown that the current crowding is stronger for wider superconducting strips but becomes weaker with an increase of the radius of the bend.…”
Section: Stationary State Of Snspdmentioning
confidence: 59%
“…It is most plausibly explained in meanders by different origins for these events. Current assisted photon counts come mostly from straight segments of the meander while fluctuation assisted photon and dark counts originate from bends [29,61,67]. This does not exclude the possibility that dark counts in the straight fragments of meanders or in nanobridges Detection mechanism of SNSPDs 20 have a different mechanism as compared to photon counts [102].…”
Section: Magnetic-field Dependence Of Photon Countsmentioning
confidence: 98%
“…Due to a current-crowding effect the current density in the 180 turnarounds of the meander structure is no longer homogeneous 27 and dark-count events most likely originate near these turnarounds, 28 but may be reduced by a more sophisticated meander design. 29 Despite this remarkable progress in understanding and optimization of SNSPD, some open questions remain, particularly in connection with the mechanism that is responsible for triggering the initial resistive cross-section. The first model 30 describing the detection mechanism in SNSPD assumed the formation of a normal-conducting hot-spot that diverts the applied bias current into the still superconducting side-walks.…”
Section: Introductionmentioning
confidence: 99%
“…This could enable transmission of quantum information and distribution of quantum entanglement [9, 10] over long distances, for the realization of quantum repeaters. Such an integrated diamond quantum photonics platform would benefit from the realization of high performance single photon detectors, with broadband photon sensitivity, that are integrated directly on the same diamond chip.Superconducting nanowire single photon detectors (SNSPDs) outperform other single photon detector technologies on several merits such as quantum efficiency [11], timing jitter, dark count rates, and broad spectral sensitivity [12,13]. SNSPDs typically consist of narrow width nanowires patterned into an ultrathin (4nm to 8nm) superconducting film, commonly made from niobium nitride or some derivative of [14].…”
mentioning
confidence: 99%